Seriousness, preventability, and burden impact of reported adverse drug reactions in Lombardy emergency departments: a retrospective 2-year characterization - Perrone V; Conti V; Venegoni M; Scotto S; Degli Esposti L; Sangiorgi D; Prestini L; Radice S; Clementi E; Vighi G (Dove Medical Press, 2014)
Valentina Perrone,1,* Valentino Conti,2,* Mauro Venegoni,2 Stefania Scotto,2 Luca Degli Esposti,3 Diego Sangiorgi,3 Lucia Prestini,4 Sonia Radice,1 Emilio Clementi,5,6 Giuseppe Vighi,2,4 1Unit of Clinical Pharmacology, Department of Biomedical and Clinical Sciences, University Hospital Luigi Sacco, Università di Milano, Milan, Italy; 2Regional Centre for Pharmacovigilance, Lombardy, Milan, Italy; 3CliCon Srl, Health, Economics and Outcomes Research, Ravenna, Italy; 4Unit of Clinical Pharmacology and Pharmacovigilance, Niguarda Ca’Granda Hospital, Milan, Italy; 5Unit of Clinical Pharmacology, CNR Institute of Neuroscience, Department of Biomedical and Clinical Sciences, University Hospital Luigi Sacco, Università di Milano, Milan, Italy; 6Scientific Institute, IRCCS Eugenio Medea, Lecco, Italy *These authors contributed equally to the work Objective: The purpose of this study was to determine the prevalence of adverse drug reactions (ADRs) reported in emergency departments (EDs) and carry out a thorough characterization of these to assess preventability, seriousness that required hospitalization, subsequent 30-day mortality, and economic burden. Methods: This was a retrospective cohort study of data from an active pharmacovigilance project at 32 EDs in the Lombardy region collected between January 1, 2010 and December 31, 2011. Demographic, clinical, and pharmacological data on patients admitted to EDs were collected by trained and qualified monitors, and deterministic record linkage was performed to estimate hospitalizations. Pharmacoeconomic analyses were based on Diagnosis-Related Group reimbursement. Results: 8,862 ADRs collected with an overall prevalence rate of 3.5 per 1,000 visits. Of all ADRs, 42% were probably/definitely preventable and 46.4% were serious, 15% required hospitalization, and 1.5% resulted in death. The System Organ Classes most frequently associated with ADRs were: skin and subcutaneous tissue, gastrointestinal, respiratory thoracic and mediastinal, and nervous system disorders. The most common Anatomical Therapeutic Chemical classes involved in admissions were J (anti-infectives and immunomodulating agents), B (blood and blood-forming organs), and N (nervous system). Older age, yellow and red triage, higher number of concomitantly taken drugs, and previous attendance in ED for the same ADR were significantly associated with an increased risk of hospitalization. The total cost associated with ADR management was €5,184,270, with a mean cost per patient of €585. Fifty-eight percent of the economic burden was defined as probably/definitely preventable. Conclusion: ADRs are a serious health/economic issue in EDs. This assessment provides a thorough estimation of their seriousness, preventability, and burden impact in a large population from a representative European region. Keywords: adverse drug reaction, preventability, economic impact, emergency department, pharmacovigilance